Albizia julibrissin Ameliorates Memory Loss Induced by Insomnia in Drosophila. (1st April 2019) - Chang, Jui-Shu; Liu, Hsin-Ping; Cheng, Jack; Chen, Chao-Jung; Hwang, Su-Lun; Tseng, Chi-Chuan; Hsu, Lee-Fen; Lin, Wei-Yong
Abstract : In clinical practice in Taiwan, Albizia julibrissin is the most prescribed Chinese herbal medicine for insomnia. Short-term insomnia and hypnotic use both attenuate cognitive functions, especially learning memory. In previous studies, A. julibrissin exhibits sedative activity, antidepressant-like effects, and protection of learning and memory against amnesia. However, whether A. julibrissin ameliorates memory loss caused by short-term sleep deprivation is not clear. We utilized the sleep-deprived Drosophila model and olfactory associative learning-memory assay to test the effects of A. julibrissin on sleep-deprivation induced memory loss. We found that A. julibrissin ameliorated 3-hour memory but not 1-hour memory or instant learning. The findings might be applied to an anticipated short-term sleep disturbance.